Toxicity of three emerging contaminants to non-target marine organisms - da Silva, Allyson Q.; de Souza Abessa, Denis Moledo [UNESP] (Springer Nature, 2019)
Coastal areas are continually impacted by anthropic activities because they shelter large urban conglomerates. Urban effluents directly or indirectly end up reaching the marine environment, releasing a large number of pollutants which include the so-called contaminants of emerging concern (CECs), since the conventional treatment plants are not effective in removing these compounds from the effluents. These substances include hormones, pharmaceuticals and personal care products, nanoparticles, biocides, among others. The aim of this study was to evaluate the toxicity of the 17α-ethinylestradiol (EE2), acetylsalicylic acid (ASA), and bisphenol-A (BPA) to two marine crustaceans and one echinoderm, evaluating the following parameters: survival (Artemia sp. and Mysidopsis juniae), embryo-larval development (Echinometra lucunter). The LC50 values calculated in the acute toxicity tests showed that the compounds were more toxic to M. juniae than to the Artemia sp. Among the three contaminants, EE2 was the most toxic (LC50-48h = 18.4 ± 2.7 mg L−1 to Artemia sp.; LC50-96h = 0.36 ± 0.07 mg L−1 to M. juniae). The three tested compounds affected significantly the embryonic development of the sea urchin in all tested concentrations, including ecologically relevant concentrations, indicating the potential risk that these contaminants may present to the marine biota.
Keywords: Acute toxicity; ASA; BPA; Chronic toxicity; EE2